Silicon-carbon composite material, silicon-carbon negative electrode material, preparation method of silicon-carbon negative electrode material and battery
By depositing and carbon covering the silicon source on porous carbon, silicon carbon negative electrode materials with good conductivity and electrochemical properties were prepared, which solved the problem of poor conductivity of the negative electrode materials of existing lithium-ion batteries, and significantly improved the cycle stability and capacity of the battery.
Patent Information
- Application Number
- CN202411973703.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The negative electrode materials of existing lithium-ion batteries, especially graphite materials, have low theoretical specific capacity and cannot meet the needs of high-energy-density battery systems. At the same time, the negative electrode materials of silicon-based negative electrodes limit their practical applications due to problems such as volume expansion effects and poor conductivity.
By depositing a silicon source on the surface and inside of the porous carbon, a silicon-carbon composite material is formed, and carbon deposited with a carbon source is treated to carbon coating to enhance conductivity and structural stability, thereby preparing a silicon-carbon negative electrode material with good conductivity and electrochemical properties.
The good conductivity and electrochemical performance of silicon-carbon composite materials have been achieved, and the first cycle efficiency, capacity and cycle stability of the battery have been improved. The first discharge specific capacity can reach 2100mAh/g, and the first Coulomb efficiency can reach more than 92%.
Smart Images

Figure CN119890256A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon coating of lithium-ion batteries, and in particular to a silicon-carbon composite material, a silicon-carbon negative electrode material and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries, with their excellent high specific energy characteristics, compact size design, excellent stability and environmental friendliness, have become the core power source in the fields of portable electronic devices and new energy vehicles, showing unlimited and broad application potential. With the increasing demand for high-performance batteries, especially the pursuit of higher capacity and stronger stability, unprecedented high standards have been put forward for the performance standards of lithium-ion batteries. In this context, the research and development and optimization of negative electrode materials, as one of the key factors determining the comprehensive performance of lithium-ion batteries, has become a key research direction for scientific research and industry.
[0003] With the booming new energy vehicle industry and the surge in demand for large-scale energy storage equipment, the limitations of graphite as a traditional negative electrode material have become increasingly prominent. Its theoretical specific capacity is only 372mAh / g, which can hardly meet the current society's urgent need for higher energy density battery systems. Silicon-based negative electrode materials have a high theoretical specific capacity and are rich in earth resources, making them a bright new star in the field of lithium-ion batteries. Among them, gas-phase silicon carbon has attracted much attention from global scientific research and industry due to its potential to be industrialized in the future. Silicon-based negative electrode materials themselves have a series of disadvantages such as volume expansion effect and poor conductivity, which limit their practical applications. Therefore, it is urgent to develop a silicon-carbon composite material with good conductivity. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a silicon-carbon composite material, a silicon-carbon negative electrode material and a preparation method thereof, and a battery. The silicon-carbon composite material of the present invention has good electrical conductivity.
[0005] To this end, the first aspect of the present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0006] S1. Mixing porous carbon and gaseous organic silicon source for reaction at 450-550°C and 100-200 kPa;
[0007] S2, carbon-coating the product obtained in S1 with a carbon source at 500-800° C. to obtain a silicon-carbon composite material;
[0008] The flow rate of the gaseous organic silicon source is 12-30 L / min.
[0009] The present invention discloses a method for preparing a silicon-carbon composite material, which specifically utilizes porous carbon as a matrix material, deposits a silicon source on the surface and inside of the porous carbon to form a silicon-carbon composite material, and then uses a carbon source for carbon precipitation treatment, performs carbon coating, enhances electrical conductivity, maintains structural stability, and finally obtains a silicon-carbon composite material. The silicon-carbon composite material has a good conductive path and therefore has good electrical conductivity. The subsequently prepared silicon-carbon negative electrode material and battery material have good electrochemical properties.
[0010] In some embodiments of the present invention, the specific surface area of the porous carbon is >1800 m 2 ·g -1 The porous carbon with a higher specific surface area can provide a certain expansion space for the gaseous organic silicon source, which is more conducive to the deposition of silicon.
[0011] In some embodiments of the present invention, the organosilicon source includes one or more of tri(trimethylsilyl)silane, monosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, methylvinyldichlorosilane, dimethylvinylchlorosilane or vinyltrichlorosilane.
[0012] In some embodiments of the present invention, the mixed reaction of the porous carbon and the gaseous organic silicon source is carried out in the presence of a protective gas; the protective gas includes nitrogen and / or argon. When the silane substance is a liquid substance, the protective gas can be used as a carrier gas to carry the liquid silane substance into the reaction container.
[0013] In some embodiments of the present invention, the volume ratio of the gaseous organic silicon source to the protective gas is (0.2-1):1.
[0014] In some embodiments of the present invention, the mixing reaction time is 5-8 hours.
[0015] In some embodiments of the present invention, the carbon coating time is 1-5 hours. For example, it can be 1, 2, 2.4, 2.8, 3.2, 3.6, 4, 5 or any value in between. If the carbon coating time is less than 1 hour, the carbon content is low, affecting the coating uniformity. If the carbon coating time is more than 5 hours, the carbon coating time is too long and the coated carbon layer is easy to break.
[0016] In some embodiments of the invention, the carbon source comprises one or more of methane, acetylene, propylene or propane.
[0017] A second aspect of the present invention provides a silicon-carbon composite material obtained by the above-mentioned method for preparing the silicon-carbon composite material.
[0018] In some embodiments of the present invention, the silicon-based composite material comprises porous carbon, silicon and soft carbon; silicon is deposited inside the porous carbon and the outside is coated with soft carbon.
[0019] The third aspect of the present invention provides a method for preparing the above silicon-carbon negative electrode material, comprising the following steps:
[0020] The silicon-carbon composite material, conductive agent, solvent and binder are mixed and dried to obtain a silicon-carbon negative electrode material.
[0021] A fourth aspect of the present invention provides a silicon-carbon negative electrode material obtained by the above-mentioned method for preparing the silicon-carbon negative electrode material.
[0022] The fifth aspect of the present invention provides a battery, including one or more of the silicon-carbon composite material made from the silicon-carbon composite material, the silicon-carbon composite material, the silicon-carbon negative electrode material made by the preparation method of the silicon-carbon negative electrode material, and the silicon-carbon negative electrode material.
[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] Figure 1 The voltage-to-capacity curve of a battery made of the silicon-carbon negative electrode material of Example 10 of the present invention is shown;
[0026] Figure 2 The scanning electron microscope image of the silicon-carbon negative electrode material of Example 3 of the present invention is shown;
[0027] Figure 3 The scanning electron microscope image of the silicon-carbon negative electrode material of Example 10 of the present invention is shown. DETAILED DESCRIPTION
[0028] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0029] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0030] A first aspect of the present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0031] S1. Mixing porous carbon and gaseous organic silicon source for reaction at 450-550°C and 100-200 kPa;
[0032] S2, carbon-coating the product obtained in S1 with a carbon source at 500-800° C. to obtain a silicon-carbon composite material;
[0033] The flow rate of the gaseous organic silicon source is 12-30 L / min.
[0034] The present invention discloses a method for preparing a silicon-carbon composite material, which specifically utilizes porous carbon as a matrix material, deposits a silicon source on the surface and inside of the porous carbon to form a silicon-carbon composite material, and then uses a carbon source for carbon precipitation treatment, performs carbon coating, enhances electrical conductivity, maintains structural stability, and finally obtains a silicon-carbon composite material. The silicon-carbon composite material has a good conductive path and therefore has good electrical conductivity. The subsequently prepared silicon-carbon negative electrode material and battery material have good electrochemical properties.
[0035] In some embodiments of the present invention, the porous carbon includes bio-based porous carbon and / or resin-based porous carbon.
[0036] In some embodiments of the present invention, the source of the bio-based porous carbon includes one or more of coconut shells, straws, rice husks, wood, bamboo, bagasse, and nut shells.
[0037] In some embodiments of the present invention, the porous carbon has a mass of 4-9 kg.
[0038] In some embodiments of the present invention, the specific surface area of the porous carbon is >1800 m 2 ·g -1 The porous carbon with a higher specific surface area can provide a certain expansion space for the gaseous organic silicon source, which is more conducive to the deposition of silicon.
[0039] In some embodiments of the present invention, the organosilicon source includes one or more of tri(trimethylsilyl)silane, monosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, methylvinyldichlorosilane, dimethylvinylchlorosilane or vinyltrichlorosilane.
[0040] In some embodiments of the present invention, the mixed reaction of the porous carbon and the gaseous organic silicon source is carried out in the presence of a protective gas; the protective gas includes nitrogen and / or argon. When the silane substance is a liquid substance, the protective gas can be used as a carrier gas to carry the liquid silane substance into the reaction container.
[0041] In some embodiments of the present invention, the volume ratio of the gaseous organic silicon source to the protective gas is (0.2-1):1.
[0042] In some embodiments of the present invention, the flow rate of the protective gas is 30-70 L / min.
[0043] In some embodiments of the present invention, the mixing reaction time is 5-8 hours.
[0044] In some embodiments of the present invention, the temperature of carbon coating is 500-800°C. For example, it can be 500, 550, 600, 650, 700, 750, 800°C or any temperature within the range. If the carbon coating temperature is lower than 500°C, it is difficult for the organic gas source to be completely carbonized, which affects the integrity of the surface coating. If the carbon coating temperature is higher than 800°C, the silicon grains are easy to grow and break during the cycle, which affects the cycle stability. Moreover, if the temperature is too high, the porous carbon material skeleton formed is easy to collapse.
[0045] In some embodiments of the present invention, the carbon coating time is 1-5 hours. For example, it can be 1, 2, 2.4, 2.8, 3.2, 3.6, 4, 5 or any value in between. If the carbon coating time is less than 1 hour, the carbon content is low, affecting the coating uniformity. If the carbon coating time is more than 5 hours, the carbon coating time is too long and the coated carbon layer is easy to break.
[0046] In some embodiments of the present invention, the carbon source is a gaseous carbon source with a gas velocity of 8-15 L / min.
[0047] In some embodiments of the invention, the carbon source comprises one or more of methane, acetylene, propylene or propane.
[0048] In some embodiments of the present invention, a method for preparing a silicon-carbon composite material comprises the following steps:
[0049] S1. Start the fluidized bed, introduce carrier gas at a flow rate of 30-70 L / min, and start heating at a heating rate of 3-10 °C / min. At the same time, weigh a certain amount of porous carbon and add it to the fluidized bed feed tank; the carrier gas is an inert gas;
[0050] S2, open the fluidized bed drain valve, close the feed valve (reactor), turn on the reactor backflush and pressure transformer backflush, and turn on the motor to adjust its speed, the speed is set to 100-200r / min, and the material is fed into the reactor during the process of heating and introducing the carrier gas; the feeding frequency is 5-15 times;
[0051] S3. When the material is completely fed into the reactor, close the feed valve and open the drain valve, wait for further heating to the reaction temperature and maintain the pressure for a certain period of time. The temperature is set to 450-550°C and the pressure holding time is 10-60min.
[0052] S4, open the silane solenoid valve, set the gas speed and reaction time, set the total gas speed to 30-80L / min, set the silane gas speed to 12-30L / min, introduce silane and maintain a certain pressure, and the silane pressure is maintained at 100-200kPa;
[0053] S5. After the silane deposition is completed, the silane is turned off and the pressure is maintained for a period of time and the temperature is continued to rise at a rate of 3-10°C / min;
[0054] S6. When the temperature reaches a certain level, set the temperature to 500-800℃, open the acetylene solenoid valve, and introduce acetylene at a pre-set gas speed of 8-15L / min for 1-5h.
[0055] S7. Turn off the acetylene and collect the vapor deposited silicon-carbon negative electrode material after the temperature drops to below 60°C.
[0056] A second aspect of the present invention provides a silicon-carbon composite material obtained by the above-mentioned method for preparing the silicon-carbon composite material.
[0057] In some embodiments of the present invention, the silicon-based composite material comprises porous carbon, silicon and soft carbon; silicon is deposited inside the porous carbon and the outside is coated with soft carbon.
[0058] The third aspect of the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0059] The silicon-carbon composite material, conductive agent, solvent and binder are mixed and dried to obtain a silicon-carbon negative electrode material.
[0060] In some embodiments of the present invention, the silicon-carbon composite material, the conductive agent, the solvent and the binder are mixed for 1-3 hours.
[0061] In some embodiments of the present invention, the drying temperature is 80-120° C. and the drying time is 24-48 hours.
[0062] In some embodiments of the present invention, the drying is performed under vacuum conditions with a vacuum degree of <100 Pa.
[0063] In some embodiments of the present invention, the mass ratio of the silicon-carbon composite material, the conductive agent and the binder is (85-93): (3-5): (2-4).
[0064] In some embodiments of the present invention, the conductive agent includes one or more of conductive carbon black, graphite, and carbon nanotubes.
[0065] In some embodiments of the present invention, the binder includes one or more of melamine formaldehyde resin (MF), carboxymethyl cellulose (NaCMC), polyethylene oxide (PAA) or polyvinyl alcohol (PVA).
[0066] In some embodiments of the present invention, the preparation method of the silicon-carbon negative electrode material specifically includes the following steps: after mixing the silicon-carbon composite material, conductive agent and binder, adding water for homogenization, after the homogenization is uniform, coating, vacuum drying, and tableting to obtain the silicon-carbon negative electrode material; the homogenization time is 1-3h, tableting, the tablet diameter is 12-14mm, and the silicon-carbon negative electrode material is obtained.
[0067] In some embodiments of the invention, the solvent comprises water.
[0068] A fourth aspect of the present invention provides a silicon-carbon negative electrode material obtained by the above-mentioned method for preparing the silicon-carbon negative electrode material.
[0069] In some embodiments of the present invention, the D50 particle size of the silicon-carbon negative electrode material is 5-6 μm.
[0070] The silicon-carbon negative electrode material of the present invention has extremely excellent electrochemical properties. The present invention adopts a vapor deposition method to improve the uniformity of silicon deposition inside the porous carbon, which can not only improve the first cycle efficiency of the battery, but also improve the capacity and cycle stability of the battery. The specific surface area of the vapor phase silicon-carbon negative electrode material prepared by this scheme can be reduced to as low as 100m 2 / g, the first discharge specific capacity can reach 2100mAh / g, and its first coulombic efficiency can reach more than 92%.
[0071] The silicon-based negative electrode material of the present invention can be used in electrochemical devices, such as secondary batteries or ion capacitors, etc. In a specific application, lithium batteries using the silicon-based material of the present invention as negative electrode materials for lithium batteries may include, but are not limited to, lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, or lithium ion polymer secondary batteries, etc. By using the silicon-based negative electrode material of the present invention, the electrochemical device has good electrochemical performance.
[0072] The fifth aspect of the present invention provides a battery, including one or more of the silicon-carbon composite material made from the silicon-carbon composite material, the silicon-carbon composite material, the silicon-carbon negative electrode material made by the preparation method of the silicon-carbon negative electrode material, and the silicon-carbon negative electrode material.
[0073] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0074] Example 1
[0075] The method for preparing the silicon-carbon composite material of this embodiment comprises the following steps:
[0076] S1. Start the fluidized bed, introduce nitrogen as carrier gas at a flow rate of 50 L / min, and start heating at a rate of 5 °C / min. At the same time, weigh 6 kg of coconut shell-based (specific surface area of 2000 m 2 ·g -1 ) porous carbon and added to the fluidized bed feed tank.
[0077] S2. Open the fluidized bed drain valve, close the feed valve (reactor), turn on the reactor backflush and pressure transformer backflush, and turn on the motor to adjust its speed. The speed is set to 150r / min, and the material is fed into the reactor during the process of heating up and introducing the carrier gas.
[0078] S3. When the material is completely fed into the reactor, close the feed valve and open the drain valve, wait for further heating to the reaction temperature and maintain the pressure for a certain period of time. The temperature is set to 500°C and the pressure holding time is 30 minutes.
[0079] S4. Open the silane solenoid valve, set the total gas velocity of gaseous monosilane and carrier gas to 50 L / min, the reaction time to 300 min, based on the total gas velocity, the proportion of monosilane gas velocity is 30%, introduce monosilane and maintain a certain pressure, and the silane pressure is maintained at 150 kPa.
[0080] S5. After the silane deposition is completed, stop introducing silane, maintain the pressure for 60 minutes, and continue to increase the temperature at a rate of 5°C / min.
[0081] S6. When the temperature reaches a certain level, set it to 580°C, open the acetylene solenoid valve, and introduce acetylene for 120 minutes at a pre-set gas speed; the acetylene gas speed is 10L / min.
[0082] S7, turn off the acetylene, collect the vapor deposited silicon-carbon composite material after the temperature drops, and collect the material when the temperature drops below 60° C. The silicon-carbon composite material has a silicon content of 48 wt %.
[0083] Example 2
[0084] The method for preparing the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that the total gas velocity in step S4 of this embodiment is 60 L / min.
[0085] Example 3
[0086] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that the total gas velocity in step S4 of this embodiment is 70 L / min. Figure 2 shown.
[0087] Example 4
[0088] The method for preparing the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that the total gas velocity in step S4 of this embodiment is 60 L / min, and the reaction time is 260 min.
[0089] Example 5
[0090] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that the total gas velocity in step S4 of this embodiment is 80 L / min, and the reaction time is 200 min.
[0091] Example 6
[0092] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that this embodiment uses 8 kg of coconut shell-based porous carbon, and the total gas velocity in step S4 of this embodiment is 60 L / min.
[0093] Example 7
[0094] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that this embodiment uses 8 kg of coconut shell-based porous carbon, and the total gas velocity in step S4 of this embodiment is 80 L / min, and based on the total gas velocity, the gas velocity of monosilane accounts for 20%.
[0095] Example 8
[0096] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that this embodiment uses 8 kg of resin-based porous carbon (with a specific surface area of 1800 m 2 ·g -1 ), the total gas velocity of this embodiment is 80L / min, and the reaction time is 290min.
[0097] Example 9
[0098] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that in step S1 of this embodiment, 8 kg of resin-based porous carbon (with a specific surface area of 1800 m 2 ·g -1 ), the total gas velocity of step S4 in this embodiment before 145 min of reaction is 60 L / min, the total gas velocity of the last 145 min is 80 L / min, and the coating time of acetylene is 3 h.
[0099] Example 10
[0100] The preparation method of the silicon-carbon composite material of this embodiment is carried out with reference to that of Example 1, and the difference from Example 1 is that this embodiment uses 8 kg of resin-based porous carbon (with a specific surface area of 1800 m 2 ·g -1 ), the total gas velocity of this embodiment is 80L / min, the reaction time is 290min; the acetylene coating time is 3h. The scanning electron microscope image of the silicon-carbon composite material of this embodiment is as follows Figure 3 shown.
[0101] Comparative Example 1
[0102] The preparation method of the silicon-carbon composite material of this comparative example is carried out with reference to Example 1, and the difference from Example 1 is that in step S4 of this comparative example, based on the total gas velocity, the gas velocity of monosilane accounts for 10%.
[0103] Comparative Example 2
[0104] The preparation method of the silicon-carbon composite material of this comparative example is carried out with reference to Example 1, and the difference from Example 1 is that in step S4 of this comparative example, based on the total gas velocity, the gas velocity of monosilane accounts for 50%.
[0105] Test Case
[0106] The silicon-carbon composite material, conductive carbon black and sodium carboxymethyl cellulose were mixed in a mass ratio of 93:4:3, deionized water was added, and the mixture was put into a pulper for slurry preparation. The mixture was homogenized for 3 hours. After the slurry was uniform, it was coated on a copper foil, dried in vacuum at 120°C for 24 hours, and pressed into a tablet with a tablet diameter of 12-14 mm to obtain a silicon-carbon negative electrode material. The specific surface area and D50 particle size of the silicon-carbon negative electrode material are shown in Table 1.
[0107] The silicon-carbon negative electrode material was transferred to an argon atmosphere glove box, and a CR2032 button half-cell was assembled for testing, with a metal lithium sheet as the counter electrode and a diaphragm as the diaphragm. The packaged button half-cell was left to stand for 10 hours and then subjected to a constant current charge-discharge cycle test at a voltage range of 0.05-2V. The results showed that under the test condition of a current of 0.05C in the first two cycles, the first coulomb efficiency was 92.5%, and the subsequent test current was 2C. Among them, the voltage-to-capacity curve of the silicon-carbon negative electrode material of Example 10 after the battery was made is shown in the figure. Figure 1 shown.
[0108] Table 1
[0109] Group First effect (%) First release mAh / g <![CDATA[Specific surface area m 2 / g]]> D50 particle size (μm) Example 1 84.2 1937.3 278 6.458 Example 2 86.7 1969.5 172 6.211 Example 3 85.3 1916.4 181 6.102 Example 4 88.2 1982.0 120 6.155 Example 5 87.3 1984.5 134 6.010 Example 6 86.1 1960.4 187 6.080 Example 7 86.5 1948.6 133 6.105 Example 8 87.6 1997.9 202 5.477 Example 9 91.7 1945.8 106 5.481 Example 10 92.5 2180.6 28 5.458 Comparative Example 1 82.6 1942.7 129 6.203 Comparative Example 2 85.6 1876.9 138 6.312
[0110] It can be seen from Table 1 that, compared with the comparative example, the electrochemical performance of the material obtained in the embodiment of the present invention is better, among which, the silicon content of the silicon-carbon composite material of Example 10 is higher, and the specific surface area of the silicon-carbon negative electrode material prepared subsequently is relatively small.
[0111] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0112] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: S1. Mixing porous carbon and gaseous organic silicon source for reaction at 450-550°C and 100-200 kPa; S2, carbon-coating the product obtained in S1 with a carbon source at 500-800° C. to obtain a silicon-carbon composite material; The flow rate of the gaseous organic silicon source is 12-30 L / min.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The specific surface area of the porous carbon is>1800m 2 ·g -1 .
3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The organic silicon source includes one or more of tri(trimethylsilyl)silane, monosilane, disilane, tetrafluorosilane, silicon trichloride, chlorosilane, hexamethyldisilane, methylvinyldichlorosilane, dimethylvinylchlorosilane or vinyltrichlorosilane.
4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The mixed reaction of the porous carbon and the gaseous organic silicon source is carried out in the presence of a protective gas; the protective gas includes nitrogen and / or argon; And / or, the volume ratio of the gaseous organic silicon source to the protective gas is (0.2-1):
1.
5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The mixing reaction time is 5-8h; and / or, The carbon coating time is 1-5h.
6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The carbon source includes one or more of methane, acetylene, propylene or propane.
7. The silicon-carbon composite material obtained by the method for preparing the silicon-carbon composite material according to any one of claims 1 to 6.
8. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: The silicon-carbon composite material obtained from the silicon-carbon composite material according to any one of claims 1 to 6 or the silicon-carbon composite material according to claim 7, a conductive agent, a solvent and a binder are mixed and dried to obtain a silicon-carbon negative electrode material.
9. The silicon-carbon negative electrode material obtained by the method for preparing the silicon-carbon negative electrode material according to claim 8.
10. A battery, characterized in that: It includes one or more of the silicon-carbon composite material made from the silicon-carbon composite material according to any one of claims 1 to 6, the silicon-carbon composite material according to claim 7, the silicon-carbon negative electrode material made by the preparation method of the silicon-carbon negative electrode material according to claim 8, and the silicon-carbon negative electrode material according to claim 9.
Citation Information
Cited By
Carbon source mixed gas CVD coated silicon carbon negative electrode material, preparation method and lithium ion battery
CN120261549A
Silicon-carbon-based composite material, preparation method thereof and application of silicon-carbon-based composite material in lithium ion battery
CN120518058A
A silicon-carbon based composite material, its preparation method, and its application in lithium-ion batteries
CN120518058B
Silicon-carbon negative electrode material, preparation method and application thereof, and battery negative electrode
CN120933333A
Preparation method for preparing silicon-carbon composite material from organic silicon and porous carbon and application of silicon-carbon composite material
CN121149176A